Russian arctic strategy: or how I learned to stop worrying and love bureaucratic politics - Justice, Daniel L. (Monterey, California: Naval Postgraduate School, 2018)
Global climate change is rapidly melting the polar ice caps and thus opening the Arctic to human activity. Russia is particularly affected by these changes as the nation with the longest Arctic coastline and a significant portion of its gross domestic product (GDP) generated above the Arctic Circle. This thesis examines how to best classify Russia’s strategy in the pre- and post-2014 periods and concludes the strategy shows a remarkable degree of continuity given the dramatic changes that occurred that year. Contrary to arguments that Russia is militarizing the Arctic or attempting to conduct a land grab, during both periods Russia has pursued an economic calculation strategy, attempting to maintain a benign political environment while at the same time steering the Arctic energy and transport sectors for the purpose of reaping economic rewards. The continuity noted in Russia’s strategy is perplexing when examined under a rational actor model. This thesis argues that a bureaucratic politics model more accurately reflects the reality of Russia’s Arctic decision making process. The ideological beliefs of the siloviki political bloc in Russia, combined with the personal financial connections of many top politicians, has led Russia to develop and maintain its Arctic strategy. Approved for public release; distribution is unlimited. Outstanding Thesis Lieutenant Commander, United States Navy http://archive.org/details/russianrcticstra1094558320